Concussions and injuries in sledge hockey: grassroots to elite participation - Sobry, A. J.; Kolstad, A. T.; Janzen, L.; Black, A. M.; Emery, C. A. (Clinical Journal of Sport Medicine, 2022)
Objective: To examine injury (including concussion) rates, location, type, mechanisms, and risk factors in sledge hockey players.